What Has Happened to Post-Christian Canada?. Issue 4 (19th February 2019) - Stackhouse, John G.
Abstract : A dozen years ago, I was sitting in a suburban Vancouver church on a Saturday afternoon, waiting for my young sons' piano recital to start. I looked around the rented facility, new to me, and noticed an impressionistic painting of the crucifixion toward the front of the sanctuary.